Formation of type 4 resistant starch and maltodextrins from amylose and amylopectin upon dry heating: A model study. (5th May 2016) - Nunes, Fernando M.; Lopes, Edgar S.; Moreira, Ana S.P.; Simões, Joana; Coimbra, Manuel A.; Domingues, Rosário M.
Highlights: Structural changes in glucosyl oligosaccharides (OS), amylose and amylopectin due to dry heating were evaluated. Amylopectin was more susceptible to heat treatments than amylose. Dehydration, depolymerization and also polymerization (for OS) were observed. Changes in Glc anomeric configuration occurred during dry thermal treatments. All these changes resulted in formation of non-digestible starch and maltodextrins. Abstract: Starch is one of the main components of human diet. During food processing, starch is submitted to high temperatures in the presence or absence of water. Thus, the main goal of this work was to identify structural modifications caused by dry heating in starch polysaccharides (amylose and amylopectin) and structurally related oligosaccharides, maltotetraose (M4) and glucosyl-maltotriose (GM3), simulating processing conditions. The structural modifications were evaluated by methylation analysis, electrospray mass spectrometry (ESI-MS), tandem mass spectrometry (ESI-MS/MS) and anionic chromatography after in vitro enzymatic digestion. Dry heating promoted dehydration, depolymerization, as well as changes in Glc glycosidic linkage positions and anomeric configuration. In oligosaccharides, polymerization was also observed. All these changes resulted in a lower in vitro digestibility, suggesting that dry heating of starch polysaccharides and related oligosaccharides may be associated with the formation of type 4 resistant starch and maltodextrins, non-digestible carbohydrates that are responsible for beneficial effects in human intestinal tract.